Eroding the Past: A Study of the Approaches of Courts towards Oral and Expert Testimony in the Salem Commonage Land Claim - Bezuidenhout, Jako (Kronos: Southern African Histories, 2024)
Since the Restitution of Land Rights Act 22 of 1994 came into operation, courts have come to attach considerable significance to historian expert testimony when ruling on land claims that made it to court. Therefore, a universal approach had to be adopted. Over the years the Supreme Court of Appeal and Constitutional Court have developed tried and tested methodologies to aid the courts in determining the weight and admissibility of a witness' testimony. In the Salem Commonage case, both the Land Claims Court and the majority of the Supreme Court of Appeal deviated from these precedents by adopting arguably a broader interpretation of the Act than intended. The case is unique in the sense that the dispute involves a commonage that was subdivided via a court order in 1940, resulting in the removal of the remaining black African population from that land. The question therefore was whether or not this group of people fulfilled the requirements for a valid claim as set out in the Act. The Land Claims Court and Supreme Court of Appeal felt that it had. The landowners applied for leave to appeal to the Constitutional Court. The application was granted, but in his judgment, Edwin Cameron agreed with the rationale of both courts, and held that there was a valid claim. This was despite the fact that the testimony of the claimants' 'star witness', Msile Nondzube, was heavily criticised by the landowners as well as a Supreme Court of Appeal judge. The Constitutional Court emphasised that the Act was an extraordinary piece of legislation and had to be interpreted in such a way so as to address the injustices of the past. This included provisions of the Act which dealt with how oral and expert evidence would be dealt with.